2022
DOI: 10.3390/pathogens11030333
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy for Alveolar Echinococcosis—A Case Series

Abstract: Benzimidazoles are the only approved drugs for the treatment of inoperable human alveolar echinococcosis but may be limited due to intolerance or, rarely, ineffectiveness. A medical second-line or salvage therapy is not available, though it is urgently needed. We report long-term follow-up data from 14 patients who underwent salvage therapy with repurposed drugs with cumulatively 53.25 patient-years. Treatment response was evaluated by both clinical outcome and image studies, preferably PET/CT. Eleven patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Only one patient treated with mefloquine in combination with ABZ and AmBD has been reported, with no treatment response after 7 months. 13 Although avoidance of palliative surgery is advised whenever possible, 3 in the case of our patient, it was performed to alleviate symptoms, need for repeated hospitals admissions (pleural effusions and recurring bacteremia episodes), and deterioration of the patient's condition despite pharmacological therapy. However, because palliative surgery can result in a worse outcome than pharmacological therapy alone, it is important to carefully choose patients who can benefit from the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Only one patient treated with mefloquine in combination with ABZ and AmBD has been reported, with no treatment response after 7 months. 13 Although avoidance of palliative surgery is advised whenever possible, 3 in the case of our patient, it was performed to alleviate symptoms, need for repeated hospitals admissions (pleural effusions and recurring bacteremia episodes), and deterioration of the patient's condition despite pharmacological therapy. However, because palliative surgery can result in a worse outcome than pharmacological therapy alone, it is important to carefully choose patients who can benefit from the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…This regimen was chosen owing to in vitro kinetics studies that showed the cycling effect and possible prolonged suppressive effect on parasite growth. 12 Recently, Burkert et al 13 reported the largest series yet, comprising 11 patients treated with different AmBD formulations and dosing regimens. Of these, three had stable disease, three had clear progression, and six developed nephrotoxicity requiring treatment cessation or reduction of dosage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used in malaria prophylaxis, mefloquine can induce strong neuropsychiatric side-effects ( Tickell-Painter et al, 2017 ). A first clinical report of an AE patient that was treated with MEF did not lead to a positive treatment response, but no adverse effects did occur either ( Burkert et al, 2022 ). This further confirms the potential lack of parasiticidal activity of MEF in an in vivo setting.…”
Section: Introductionmentioning
confidence: 99%